Analisis Peran Program Jaminan Kesehatan Nasional (JKN) dalam Mengurangi Beban Finansial Pasien: Studi Literature - Zebua, Cynthianoor Fitriana Puteri; Ardhila, Diva; Yuriska, Yuriska; Gurning, Fitriani Pramita (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
Insurance or coverage is an agreement, whereby an insurer binds himself to the insured by receiving a premium, to provide compensation to him because of a loss, damage or loss of profits that may be suffered due to an uncertain event (Book of Commercial Laws) Criminal Code) of the Republic of Indonesia Article 246). The interesting things to analyze are first, the form of worker protection in the National Health Insurance (JKN) program and second, the problems in its application. The model used in this work is a literature review, in which information that is suitable for the problem being investigated is sought from various references and sources. Following is the selection of scientific articles: The selection of scientific articles is done by searching the PubMed, ScienceDirect and Google Scholar databases for relevant articles published in the 2019-2023 period. The selected articles must meet the established inclusion and exclusion criteria. Determination of Inclusion and Exclusion Criteria: The inclusion criteria used in this study include articles on "Analysis of the effectiveness of health insurance in reducing the patient's financial burden" and studies conducted at the provincial or national level. Exclusion criteria were articles that did not meet the inclusion criteria, articles that were not related to the research topic, and articles published before 2019. Keywords: Insurance, JKN, Patient Finances